A Novel Index of the Performance of Mytilus galloprovincialis to Improve Commercial Exploitation in Aquaculture - Babarro, Jose M. F.; Filgueira, Ramón; Padín, Xosé A.; Longa Portabales, M. Angeles (Frontiers in Marine Science, 2020)
Estuarine environments are highly heterogeneous habitats where numerous organisms interact with each other. Aquaculture systems encompass such interactions, and the eventual yields depend on how the cultivated species respond to the environmental heterogeneity. Marine mussels are calcifying organisms that rely on calcium carbonate shell and byssus filaments secreted during their lifetime to protect soft vital tissues against aggressive, hydrodynamic environments and the actions of predators and competitors. Nevertheless, these protective structures can be energetically costly, depending on the environment, thus affecting the energy allocation patterns in the organism. Consequently, other important fitness parameters for the aquaculture industry, such as soft tissue condition and market value, may also be affected. Here, we present a spatial and temporal analysis of the protective and fitness responses in the mussel Mytilus galloprovincialis with the aim of obtaining a better understanding of the inter-location variability in survival and performance and the corresponding main environmental drivers. A novel, intuitive ecological index that measures the impact of both protective and fitness strategies was developed and is discussed in relation to cultivation timing. The data presented provides the basis for understanding the natural variability in energetic requirements for different vital tissues in bivalve mollusk that support survival and growth. We report the scientific basis for management actions aimed to shortening the cultivation cycle in the aquaculture sector. These actions are based on the combined use of the PROFIT index and other aquaculture practices (e.g. modifying density). PROFIT helps to identify when the quality of the product, understood as PROtection and FITness strategies, would be best suited for the market. Highlights: - PROFIT is a novel, simple eco-physiological index for use in the cultivation of marine mussels - Consideration of protective tissues and yield in cultivated marine bivalves is needed for better comprehension of energetic trade-offs during the life cycle - Innovations in aquaculture practices, here with the marine mussel Mytilus galloprovincialis as a case study, should consider new indicators like PROFIT (and others) for better management of the natural resource and for differentiating production areas or exploitation methods